The principles of flight for pilots - Swatton, P. J. (Peter J.) (Aerospace series (Chichester, England), 2011)
Organised and written as an accessible study guide for student pilots wishing to take commercial ground examinations to obtain ATPL or CPL licenses, Principles of Flight for Pilots also provides a reliable up-to-date reference for qualified and experienced personnel wishing to further improve their understanding of the Principles of Flight and related subjects. Providing a unique aerodynamics reference tool, unlike any book previously Principles of Flight for Pilots explains in significant depth all the topics necessary to pass the Principles of Flight examination as required by the EASA sylla.